Major shortcomings of existing pension schemes and fundamental requirements for a new national income-related scheme - Collins, C. (Statistical and Social Inquiry Society of Ireland, 1977)
I would like first of all on behalf of the Parliamentary Secretary to the Minister for Social Welfare to thank the Statistical and Social Inquiry Society of Ireland for arranging this symposium on the Green Paper entitled "A National Income-Related Pension Scheme". As stated in the foreword, the Parliamentary Secretary hopes that there will be detailed and widespread study and discussion of the ideas contained in the Paper. This is the first discussion of the Green Paper to be arranged since the Paper was published and I welcome the opportunity to outline the main shortcomings we see in the present pension system in Ireland and possible ways in which these might be overcome. In doing so I will try to draw together various questions raised throughout the Green Paper so as to focus the discussion on the issues of major importance. I might mention also that I have tried to avoid trespassing on areas which will be dealt with more appropriately by the second speaker, Mr. Honohan, who provided the necessary actuarial expertise in the preparation of the Green Paper, and to whom we in the Department feel very much indebted.
Symposium on the Government Green Paper "A National Income-Related Pension Scheme"
Read before the Society, 16 December 1976
Keywords: Irish pensions policy; National Income-Related Pension Scheme; Social insurance; 314.15